2012
DOI: 10.1111/j.1365-2966.2012.21630.x
|View full text |Cite
|
Sign up to set email alerts
|

Free motion around black holes with discs or rings: between integrability and chaos - II

Abstract: We continue the study of time-like geodesic dynamics in exact static, axially and reflection symmetric space-times describing the fields of a Schwarzschild black hole surrounded by thin discs or rings. In the previous paper, the rise (and decline) of geodesic chaos with ring/disc mass and position and with test particle energy was revealed on Poincaré sections, on time series of position or velocity and their power spectra, and on time evolution of the orbital 'latitudinal action'. In agreement with the KAM th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The results of [11,12] point in the direction of the proof presented in this paper, whereas the results of [4,5,34,47] are mathematically inconsistent and the conclusions derived from them must be reformulated in light of the present approach. Since the stability criterion obtained and the adiabatic invariance analysis are both local, we can extend our formalism to black holes surrounded by razor-thin disks or rings [4,15,30,31,34], provided the metric outside the horizon has the form (5) and the orbit does not cross the horizon. In particular, the results obtained in [34,47] …”
Section: Discussionmentioning
confidence: 99%
“…The results of [11,12] point in the direction of the proof presented in this paper, whereas the results of [4,5,34,47] are mathematically inconsistent and the conclusions derived from them must be reformulated in light of the present approach. Since the stability criterion obtained and the adiabatic invariance analysis are both local, we can extend our formalism to black holes surrounded by razor-thin disks or rings [4,15,30,31,34], provided the metric outside the horizon has the form (5) and the orbit does not cross the horizon. In particular, the results obtained in [34,47] …”
Section: Discussionmentioning
confidence: 99%
“…In such a case, the electromagnetic field affects the geometry of the spacetime and as a particular consequence of this influence, we found that the system allows off-equatorial orbits even for neutral test particles. The interplay between the chaotic and ordered motion of test particles in the exactly given static field of a massive source encircled by a disk or a ring was also recently investigated (Suková & Semerák 2013;Semerák & Suková 2012. Nevertheless, in the following, we intend to focus on a more realistic model in which the rotation of the central object is included.…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12][13][14][15] In the above cases the Kerr black hole hypothesis 16 is assumed to hold for the SMBH. However, it has been shown that spacetimes diverging from the Kerr by a deformation parameter can also result in non-integrable systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence analysis and RQA have already been applied to detect the onset of chaos in various non-integrable relativistic systems. 13,14,[36][37][38][39] In these systems the RQA indicator DIV defined as an inverse value of the length of the longest diagonal line found in the RP…”
mentioning
confidence: 99%